2009
DOI: 10.1242/jcs.053702
|View full text |Cite
|
Sign up to set email alerts
|

Human RPA phosphorylation by ATR stimulates DNA synthesis and prevents ssDNA accumulation during DNA-replication stress

Abstract: under non-stress conditions, the mutant cells were severely deficient in the amount of DNA synthesis occurring during replication stress. These cells also had abnormally high levels of chromatin-bound RPA, indicative of increased amounts of single-stranded DNA (ssDNA) and showed defective recovery from stress. Cells replaced with the mutant RPA2 also generated G1 cells with a broader DNA distribution and high levels of apoptosis following stress, compared with cells expressing wild-type RPA2. Surprisingly, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 45 publications
6
155
0
2
Order By: Relevance
“…5A). These results were further strengthened by the analysis of phospho-S33-RPA foci accumulation, a marker of DNA replication lesions (50), which also supported a specific role of p53(WT) lost in p53(H115N)-expressing cells (Fig. 5B).…”
Section: P53(wt) Promotes Rpa Foci Accumulation In a Manner Dependent Onmentioning
confidence: 55%
See 1 more Smart Citation
“…5A). These results were further strengthened by the analysis of phospho-S33-RPA foci accumulation, a marker of DNA replication lesions (50), which also supported a specific role of p53(WT) lost in p53(H115N)-expressing cells (Fig. 5B).…”
Section: P53(wt) Promotes Rpa Foci Accumulation In a Manner Dependent Onmentioning
confidence: 55%
“…Interestingly, in H1299 cells expressing tetracycline-regulated p53 variants (27), p53(WT) caused a statistically significant increase (1.5-fold; P = 0.0169) in the IC 50 value following MMC treatment. In contrast, p53(H115N) expression did not alter the IC 50 value (P = 0.5986), despite the increase in both p53 and p21 expression levels ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4B). ATR kinase initiates the signaling cascade in response to the collapse of stalled replication forks and promotes phosphorylation of RPA at Ser 33 (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that RPA2 has a distinctive pattern of phosphorylation in many tumour cell lines in response to replication and CHK1 inhibitors (Anantha et al, 2007;Liu et al, 2012). There is general agreement that Ser33 is a phosphorylation target for activated ATR (Anantha et al, 2007;Vassin et al, 2009). In contrast, Ser4/8 is mainly phosphorylated through ATM or DNAPK activity (Liu et al, 2012).…”
Section: Figure3 7 Decreased Chk1 Transcription In Htert-mentioning
confidence: 99%